Development of nanogap based dielectric biosensor for label-free medical diagnostic analytical measurement - A., Mat Taib; Uda, Hashim, Prof. Dr.; N. A., Yusof; Th. S., Dhahi (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology (MUCEET) 2009 organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis, 20th - 22nd June 2009 at MS Garden Hotel, Kuantan, Pahang, Malaysia.